Theoretical And Experimental Evaluation Of Co2 Emissions From Commercial Diesel B10 And Biodiesel B100 - Ramírez Velasco, Carlos Alonso; Pérez Ortega, Diego Javier; Pereira Martínez , Ricardo Ignacio; Bolaños Alomía, Fabio Andrés (Ingeniería Solidaria, 2020)
Introduction: This article is a product of the research “Theoretical and experimental evaluation of CO2emissions from commercial diesel B10 and biodiesel B100”, developed at the Universidad Cooperativa de Colombia and the Universidad Mariana of Pasto, in the years 2018 and 2019.Problem: The use of fossil diesel B10 and biodiesel B100 in engines creates CO2emissions and it is necessary to quantify them.Objective: To quantize the CO2emissions from the exhaust of an engine, using B10 and B100 fuels.Methodology: The motor of an electric power plant was subjected to three power settings. Two factors were taken into account: the type of diesel and power generated, and the effect on the CO2emissions.Results: CO2inventories and emissions are higher with B10, although this is not always the case. They are also higher when more power is generated.Conclusion: The higher CO2emission does not depend on the type of fuel, but on the chemical composition of the fuel.Originality: In the world they are made CO2inventories, these are usually done theoretically; however, with this research, actual measurements were made.Limitations: For reasons of noise and smoke hazards, the experiment was done in an open space. This would have caused slight errors in the results, due to abrupt changes in the climate and variability in the weighing of the fuel.